Self-Medication for Chronic Pain Using Classic Psychedelics: A Qualitative Investigation to Inform Future Research - Bornemann, Julia; Close, James B.; Spriggs, Meg J.; Carhart-Harris, Robin; Roseman, Leor (Frontiers in Psychiatry, 2021)
Abstract Background: Chronic Pain is among the leading causes of disability worldwide with up to 60% of patients suffering from comorbid depression. Psychedelic-assisted therapy has recently been found effective in treating a host of mental health issues including depression and has historically been found to be useful in treating pain. Reports of self-medication for chronic pain using psychedelic drugs have been widely documented, with anecdotal evidence indicating widespread success in a range of pathologies. Aims: In preparation for an upcoming trial, to better understand how those with lived experience of chronic pain self-medicate with psychedelic drugs, and to establish, in detail, their therapeutic protocols and practices for success. Methods: As part of patient-involvement (PI) for an upcoming trial in this population, 11 individuals who reported self-medicating with psychedelic drugs took part in a one-hour semi-structured discussion, which was then transcribed and thematically analysed. Results: Across a range of psychedelic substances and doses, reported pain scores improved substantially during and after psychedelic experiences. Two processes, Positive Reframing and Somatic Presence, were reliably identified as playing a role in improvements in mental wellbeing, relationship with pain, and physical (dis)comfort. Inclusion of other strategies such as mindfulness, breathwork, and movement were also widely reported. Due to the data’s subjective nature, this paper is vulnerable to bias and makes no claims on causality or generalisability. Together, these results have been used to inform study design for a forthcoming trial. Conclusion: This pre-trial PI work gives us confidence to test psychedelic therapy for chronic pain in a forthcoming controlled trial. The results presented here will be instrumental in improving our ability to meet the needs of future study participants. Keywords: Psychedelic, Chronic Pain, Self-medication, Patient and Public Involvement, PPI, Thematic Analysis.